P192 A pilot study to assess the influence of β2-adrenoceptor polymorphism on small airway function and asthma control. (14th November 2013) - Manoharan, A; Lipworth, J; Short, PM; Anderson, WJ; Williamson, PA; Berg, J; Lipworth, BJ
Abstract : Introduction and Objectives: It is increasingly recognised that small airway dysfunction is associated with suboptimal asthma control. We have previously reported that β2-adrenoreceptor polymorphism at position 16 (i.e. Arg/Gly) is not related to FEV1 or airway hyper-responsiveness in persistent asthmatics. 1 However effects of β2-adrenoreceptor polymorphism on the small airways are not known. This pilot study in a different cohort of patients evaluated the effects of β2-adrenoreceptor polymorphism on small airway function and asthma control. Impulse oscillometry (IOS) was used to assess small airway function along with FEF25–75 . IOS is an effort independent test performed during normal quiet tidal breathing and is able to discriminate between changes in central and peripheral airways. Resistance at 5 Hz (R5) and 20 Hz (R20) indicate total and central airway resistance respectively - the difference between R5 and R20 indicates peripheral airway resistance. Asthma control was assessed using the Asthma Control Questionnaire (ACQ-5). Methods: We collected spirometry, IOS and ACQ data from patients attending a secondary care asthma clinic. A total of 100 patients all taking inhaled corticosteroids (20% taking long acting beta-agonists) were included with a mean: age 39.2 year FEV1 88.4%, FEF25–75 % 55.5%, R5%162%, R5-R20 0.07 kPa/l/s, ACQ-5 1.70 Results: 48% (n = 48) had 1 or 2 copies of the Arg allele (i.e. Arg/Arg or Arg/Gly genotypes) while 52% (n = 52) had no copies of the Arg allele (i.e. Gly/Gly genotype). There was no significant difference between genotypes in terms of FEV1, FEF25–75, R5, R5-R20 or ACQ. Furthermore there was no significant effect of LABA according to Arg/Gly polymorphism. Reference: 1. Manoharan A, Anderson WJ, Lipworth BJ. Influence of β2-adrenergic receptor polymorphism on methacholine hyperresponsiveness in asthmatic patients. Ann Allergy Asthma Immunol 2013;110: 161–164